Superconducting Through-Substrate Vias on Sapphire Substrates for Quantum Circuits - Kiyotaka Mukasa; Yusuke Nuruki; Hayato Kubo; Yoshihide Narahara; Motohiro Umehara; Kazuyuki Fujie (IEEE Transactions on Quantum Engineering)
Sapphire substrates have recently been recognized for their potential to improve the coherence time of superconducting qubits. However, due to challenges in via fabrication, silicon substrates have been predominantly used for qubits. In this study, we fabricated vias on sapphire substrates using lasers and deposited TiN films by chemical vapor deposition. Cross-sectional views of the via confirmed uniform thickness of the TiN film along the via wall. In addition, the TiN film exhibited a superconducting transition at 4.5 K, demonstrating the successful deposition of a high-quality homogeneous superconducting film. This represents the first example of realizing superconducting through-substrate vias on sapphire substrates, a crucial first step toward achieving the 3-D integration of qubits while maintaining coherence time.